Solar Proton Transport within an ICRU Sphere Surrounded by a Complex Shield: Combinatorial Geometry - Wilson, John W.; Slaba, Tony C.; Badavi, Francis F.; Reddell, Brandon D.; Bahadori, Amir A. (My University, 2015)
The 3DHZETRN code, with improved neutron and light ion (Z (is) less than 2) transport procedures, was recently developed and compared to Monte Carlo (MC) simulations using simplified spherical geometries. It was shown that 3DHZETRN agrees with the MC codes to the extent they agree with each other. In the present report, the 3DHZETRN code is extended to enable analysis in general combinatorial geometry. A more complex shielding structure with internal parts surrounding a tissue sphere is considered and compared against MC simulations. It is shown that even in the more complex geometry, 3DHZETRN agrees well with the MC codes and maintains a high degree of computational efficiency.
Citation: Wilson JW, Slaba TC, Badavi FF, Reddell BD, and Bahadori AA 2015 Solar Proton Transport within an ICRU Sphere Surrounded by a Complex Shield: Combinatorial Geometry NASA/TP-2015-218980 NASA Langley Research Center: Hampton, VA http://ntrs.nasa.gov/search.jsp?R=20160001628
Keywords: RADIATION TRANSPORT; Combinatorial Analysis; Neutrons; Spheres; Tissues (Biology); Three Dimensional Models; Spacecraft Shielding